A New Approach to Islamic Inheritance Law Education in Pesantren - Sumarno Sumarno; Indah Musfiratul; Kisbuloh Kisbuloh (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2024)
Ilmu mawarits, or Islamic inheritance law, holds significant importance in Muslim communities as it ensures the fair distribution of a deceased person's estate in accordance with the Qur'an and Hadith. Despite its importance, the study and application of ilmu mawarits are often neglected in modern times, leading to conflicts and misunderstandings within families. The Centre for Mawarith Studies (CMS) at Universitas Darussalam Gontor aims to address this issue by implementing innovative educational approaches to enhance the understanding and application of Islamic inheritance law. This research aims to explore the thoughts and movements of CMS in educating ilmu mawarits within pesantrens, providing insights into its innovative curriculum, teaching methods, and the overall impact on the community's understanding of Islamic inheritance law. A qualitative case study method was employed at the CMS of Universitas Darussalam Gontor. Data were collected through in-depth interviews, participatory observations, and document analysis involving 30 participants, including CMS administrators, educators, and students. Thematic analysis was used to analyze the data, ensuring validity through triangulation techniques. The findings reveal that CMS has significantly influenced the approach to teaching ilmu mawarits by focusing on practical applications and interactive learning methods. This approach has successfully enhanced the understanding and skills of students, making Islamic inheritance law more accessible and applicable in daily life. The study recommends further development of innovative educational methods and the integration of practical applications in the teaching of ilmu mawarits. Additionally, expanding CMS programs to other Islamic educational institutions could further promote the understanding and application of Islamic inheritance law across broader communities.